Energy consumption and the size of the informal economy - Mustafa Metin Basbay; Ceyhun Elgin; Orhan Torul (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
In this paper, the authors empirically investigate the relationship between energy consumption and the size of the informal economy. Relying on panel data regression models, their results show that at the aggregate level, energy intensity is inversely related to the size of the informal sector, providing actual empirical evidence on the presence of high labor and low capital intensity in the informal economy. Furthermore, the authors also find some support towards the presence of non-linearity and asymmetry in this relationship.
Keywords: O17; O13; P48; E26; 330; informal sector; energy consumption; panel data